Role of Migrant Labours in the Kerala State Economy - Aswani T. D.; Shivashankar Bhat, (International Journal of Management, Technology and Social Sciences (IJMTS), 2022)
Purpose: Migrant labour contributes to the economic growth of the economy. Agriculturalists, manufacturers, and service providers are increasingly turning to poor migrant labour for operations, according to field evidence and micro studies. Employers can practise a hire-and-fire strategy with migrant workers since they supply the most flexible workforce. Kerala has a large number of cyclical migrant workers. These workers have been crucial in keeping and growing Kerala's economy. The impact of migration of labour can be analysed in areas like the labour market, the public purse (tax revenue) and economic growth. The goal of this research is to see how much native labour is available in the rural labour market and to look at the current migratory worker structure. Methodology: The methodology used in this study is Descriptive Research, which is mainly concerned with secondary data sources. Books, newspapers, journals, articles, and government websites are used to gather secondary data. Originality: The breadth and function of migrant workers in Kerala's present labour market, as well as the availability of native labour in the casual rural labour market, are all discussed. Value: By examining the sectoral-wise distribution of employment, the study will aid in determining the role of migrants in the Kerala economy. Findings: In India, the rural labour market is shifting away from agriculture and toward secondary and tertiary industries. The overall employment in agriculture is declining every year whereas in the industrial and services sectors there is a gradual increase in the workforce. The lack of manual labourers is a key issue for the government. The influx of migrant workers into Kerala's labour market provided relief to the state's manual labour shortage since they provided a cheaper labour force. Migrant workers play a vital role in the labour supply and play a significant part to the state's economic development by imparting labour for a variety of economic activities that would otherwise be impossible to sustain owing to a labour shortage. Paper Type: Descriptive study